Effectiveness of Group Counseling Services with Motivational Interviewing (MI) Techniques In Increasing Learning Motivation In Students - Nasution, Ahmad zaki Ilman; Syukur, Yarmis; Sukma, Dina (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to determine the effectiveness of group counseling services using motivational interviewing (MI) techniques in increasing student learning motivation at the Mawaridussalam Islamic boarding school. This research uses a quantitative approach with pre-experimental methods. This research uses a one group pretest-posttest design (One Group Pretest-Posttest). Data analysis was carried out using descriptive statistical methods. The subjects of this research were 8 students who were selected using purposive sampling techniques. Research data was collected using a learning motivation scale. The results of the Hypothesis Test analysis (t test) show a Sig (2-tailed) value of 0.001<0.05. It can be concluded that there is a significant difference in students' learning motivation before and after being given treatment in the form of group counseling services using motivational interviewing (MI) techniques. Because the t-test value of P<0.05 is (0.001<05), the findings show that the use of group counseling services with motivational interviewing (MI) techniques in increasing students' learning motivation has a significant effect.